PENINGKATAN CITRA MELALUI PROGRAM POLISI SAHABAT PETANI DALAM PEMBERITAAN MEDIA ONLINE - Bafiki Putra, Al Bhaihaqi; Lailiyah, Fatihatul; Ramadhani, Rakhmad Saiful (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2024)
In recent years, there have been indications of public doubt regarding the role and function of the Police as law enforcers after many cases involving internal police that have attracted public or community attention, starting from the case of Inspector General of Police Ferdi Sambo who shot his subordinates, the drug case involving former East Java Police Chief Inspector General of Police Teddy Minahasa, and several other cases. This study aims to analyze the critical discourse of news about the